An asymptotic theory for the re-equilibration of a micellar surfactant solution - Griffiths, I; Bain, C; Breward, C; Chapman, S; Howell, P; Waters, S (2011)
Micellar surfactant solutions are characterized by a distribution of aggregates comprised predominantly of pre-micellar aggregates (monomers, dimers, trimers, etc.) and a region of proper micelles close to the peak aggregation number, connected by an intermediate region containing a very low concentration of aggregates. Such a distribution gives rise to a distinct two-timescale re-equilibration following a system dilution, known as the 1 and 2 processes, whose dynamics may be described by the Becker–Döring equations. We use a continuum version of these equations to develop a reduced asymptotic description that elucidates the behavior during each of these processes.